Medical Anthropology and Ethnography. An approach to a case study on immigrant health conditions in Spanish society - Alejandro Goldberg (AM. Rivista della Società Italiana di Antropologia Medica, 2001)
Medical Anthropology and Ethnography.An approach to a case study on immigrant health conditions in Spanish society